2006
DOI: 10.1128/jb.00947-06
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 2-Bromoethanesulfonate as a Selective Inhibitor of the Coenzyme M-Dependent Pathway and Enzymes of Bacterial Aliphatic Epoxide Metabolism

Abstract: Bacterial growth with short-chain aliphatic alkenes requires coenzyme M (CoM) (2-mercaptoethanesulfonic acid), which serves as the nucleophile for activation and conversion of epoxide products formed from alkene oxidation to central metabolites. In the present work the CoM analog 2-bromoethanesulfonate (BES) was shown to be a specific inhibitor of propylene-dependent growth of and epoxypropane metabolism by Xanthobacter autotrophicus strain Py2. BES (at low [millimolar] concentrations) completely prevented gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…The present work expands on our previous work (16) showing BES to be an inactivator of bacterial epoxide metabolism by determining the targets and mechanisms of BES inhibition and inactivation. R-HPCDH and 2-KPCC were reversibly inhibited by BES, whereas 2-KPCC was additionally inactivated by the highly specific and irreversible alkylation of the interchange thiol that interacts with the substrate 2-KPC within the enzyme active site.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…The present work expands on our previous work (16) showing BES to be an inactivator of bacterial epoxide metabolism by determining the targets and mechanisms of BES inhibition and inactivation. R-HPCDH and 2-KPCC were reversibly inhibited by BES, whereas 2-KPCC was additionally inactivated by the highly specific and irreversible alkylation of the interchange thiol that interacts with the substrate 2-KPC within the enzyme active site.…”
Section: Discussionsupporting
confidence: 49%
“…Time-and Concentration-dependent Inactivation of 2-KPCC by BES-A previous study showed that the addition of BES to cell extracts of X. autotrophicus resulted in an irreversible loss of epoxide carboxylation activity that could only be restored by adding purified active 2-KPCC back to the cell extracts, suggesting that 2-KPCC is irreversibly inactivated by BES (16). To investigate this in more detail, 2-KPCC was incubated anoxically in the presence of DTT with various concentrations of BES, and samples were removed at various time points and assayed for activity after removal of BES as described above.…”
Section: Kinetic Characterization Of Bes Inhibition Of R-hpcdh-a Kinementioning
confidence: 99%
See 2 more Smart Citations
“…Coenzyme M is an essential terminal methyl carrier in methanogenesis (Graham & White, 2002;Thauer, 1998) and promotes growth in some methanogenic members of the Archaea (Miller et al, 1986;Sprenger et al, 2000;. Coenzyme M has a role not only in the methanogenesis pathway in the Euryarchaeota, but also in the utilization of short-chain alkenes, as demonstrated in recent studies on propylene-, ethyleneand vinyl chloride-utilizing bacteria (Allen et al, 1999;Boyd et al, 2006;Coleman & Spain, 2003a, b;Danko et al, 2006;Mattes et al, 2005). Emission of trace amounts of methane is generally observed in the growing cultures of almost all Archaeoglobus species, but they are unable to grow by methanogenesis.…”
Section: K Mori and Others 814mentioning
confidence: 92%